Design and Experiments of Low Cost Teleoperation System - Adha Imam Cahyadi; Ng Khin Hooi; Anugrah Persada; Rubiyah Yusof; Yoshio Yamamoto (IAES International Journal of Robotics and Automation (IJRA), 2012)
In this work, a teleoperation system consists of two planar SCARA manipulators is developed. The manipulators are constructed using basic low cost aluminum bars as well as cheap electronic circuitry and software. Modeling, system identification, individual control and teleoperation control are proposed. Finally, experiments are also performed to verify the effectiveness of the design.Index Terms—Teleoperation systems, PID control, System identification, position control.DOI: http://dx.doi.org/10.11591/ijra.v1i1.272